The Impact of Timber Legality Verification System (SVLK) on Indonesian Plywood Export Market - Dwi Putro Notonegoro (Universitas Negeri Malang, 2018)
This paper tried to estimate the effect of regulation in the plywood export market, not only on the quantity export but also on the revenue earned from the product. Using panel data of this market from 2000 to 2014 and involving 58 countries as trading partner, gravity model which had been used in many studies of international trade will be adapted. Three models which were used in this study, such as pooled least square, fixed and random effect model, found an indication that quantity exported and revenue earned after the implementation of the regulation was less than before. In pooled regression model, the quantity and revenue from plywood export decreased more than 95 per cent. In addition, fixed and random effect model showed similar result with the pooled regression model. Keywords: Timber Legality Verification System (SVLK), gravity model JEL Classification: F14; F23